BAZIS Scholarship Funds and Student Achievement - Roikhan MA (Universitas Islam Negeri Raden Mas Said Surakarta, 2016)
This research aims to analyze the effect of the distribution of BAZIS (Council for Zakat Administration) scholarship funds on student achievement in East Jakarta. Data has been gathered from BAZIS scholarship recipients in the period 2014 to 2015, with the sample selected by means of random sampling. Validity, reliability, classic assumption, different and multiple regression tests are employed to analyze the data. The results statistically show that the variables of achievement can be explained by distribution variable, usage pattern, controlling and gender in the amount of 96,6% and the remaining 3,4% is influenced by other variables. This research argues that independent variables have significant effect on student learning achievement.Â Keywords:Â learning achievement, BAZIS, zakatÂ